2004
DOI: 10.1099/ijs.0.02920-0
|View full text |Cite
|
Sign up to set email alerts
|

Collimonas fungivorans gen. nov., sp. nov., a chitinolytic soil bacterium with the ability to grow on living fungal hyphae

Abstract: A polyphasic approach was used to describe the phylogenetic position of 22 chitinolytic bacterial isolates that were able to grow at the expense of intact, living hyphae of several soil fungi. These isolates, which were found in slightly acidic dune soils in the Netherlands, were strictly aerobic, Gram-negative rods. Cells grown in liquid cultures were flagellated and possessed pili. A wide range of sugars, alcohols, organic acids and amino acids could be metabolized, whereas several di- and trisaccharides cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
127
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 25 publications
3
127
0
1
Order By: Relevance
“…The 16S rRNA gene fragment of the corresponding OTUs presented 99 and 97% similarity with that of C. fungivorans and M. petroleiphilum. C. fungivorans was previously described as a chitinolytic bacterium and to grow at the expense of different soil fungi in soil (9). These species differ from those described by Artursson and Jansson (4) as being preferentially associated with AM fungi, but their study was made directly in a fallow soil and not on roots.…”
Section: Discussionmentioning
confidence: 81%
“…The 16S rRNA gene fragment of the corresponding OTUs presented 99 and 97% similarity with that of C. fungivorans and M. petroleiphilum. C. fungivorans was previously described as a chitinolytic bacterium and to grow at the expense of different soil fungi in soil (9). These species differ from those described by Artursson and Jansson (4) as being preferentially associated with AM fungi, but their study was made directly in a fallow soil and not on roots.…”
Section: Discussionmentioning
confidence: 81%
“…Colony PCR was performed using fresh colonies that were taken from 10-fold-diluted TSB agar after 24 h of incubation (Rademaker et al, 1997). Visual comparison of the banding profiles and UPGMA clustering of strains using Pearson's product-moment correlation coefficients in the Bionumerics version 3.5 software package revealed that the majority (n518) of the new isolates fell within clusters B and D described previously (De Boer et al, 2004). Only one of the new isolates fell in cluster A.…”
mentioning
confidence: 82%
“…Collimonas strains have the interesting ability to grow at the expense of living fungal hyphae (mycophagy), albeit under laboratory conditions (De Boer et al, 2001. The taxonomy of these bacteria was examined using genomic fingerprinting (BOX-PCR), sequencing of 16S rRNA genes and physiological characterization, which revealed four clusters of strains (De Boer et al, 2004). So far, only cluster C strains have been formally classified, as the novel species Collimonas fungivorans.…”
mentioning
confidence: 99%
See 2 more Smart Citations